Signal timing and geometric design at contraflow left-turn lane intersections - Rongwei Guo; Jinli Liu; Qun Zhao; Yi Qi (International Journal of Transportation Science and Technology, 2022)
As a type of innovative intersection, Contraflow left-turn lane (CLL) intersection, has been increasingly implemented at the signalized intersections for increasing the leftturn capacity. This study developed a systematic method for determining the length of CLL and the signal timing plan for implementing CLL at signalized intersections. At first, the signal timing and geometric design requirements in the implementation of CLL were analyzed. Then, these requirements were thoroughly considered in the development of the proposed method. A case study was conducted for evaluating the operational benefits of redesigning a real-world CLL intersection using the recommended signal timing plan and CLL lengths. The results of the case study show that the redesigned CLL intersection outperforms the existing CLL intersection in terms of the average traffic delay, average vehicle travel time, and average queue length, and the CLL intersection can achieve its best performance at the recommended CLL lengths. These results indicate that the proposed method can provide useful guidelines to traffic engineers in the implementation of this innovative intersection design.